2012
DOI: 10.7306/gq.1023
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary environment and tectonic controls of the Snochowice Beds (Lower Jurassic, western margin of the Holy Cross Mountains, Poland)

Abstract: The Snochowice Beds rep re sent the low er most part of the Lower Ju ras sic suc ces sion in the west ern part of the Me so zoic mar gin of the Holy Cross Moun tains (Cen tral Po land). This thick, grav elly has a dif fer ent lithological char ac ter to other Lower Ju ras sic sandy and fine-grained de pos its. Eight lithofacies have been dis tin guished, mainly grav elly and sandy, grouped into four ge netic as so ci a tions: Mmas sive grav els, in ter preted as clast-rich de bris flow de pos its, G -hor i zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It is important to emphasize the lithologically diverse contact of Upper Triassic sediments with the deposits of the Middle Jurassic. In the studied area, red claystones and mudstones of Keuper are in contact with Callovian gaizes, but in other places, for example, further southeast, the Upper Triassic is represented by yellowish‐grey sandstones that are directly covered by dark‐grey clays of Bathonian age (Kozłowska et al, 2016). Palynological studies have shown that these grey deposits correspond to the Rhaetian character of the waning episode of Triassic sedimentation (Kozłowska et al, 2016).…”
Section: Lithology Mineralogy Physical and Mechanical Properties Of T...mentioning
confidence: 95%
See 2 more Smart Citations
“…It is important to emphasize the lithologically diverse contact of Upper Triassic sediments with the deposits of the Middle Jurassic. In the studied area, red claystones and mudstones of Keuper are in contact with Callovian gaizes, but in other places, for example, further southeast, the Upper Triassic is represented by yellowish‐grey sandstones that are directly covered by dark‐grey clays of Bathonian age (Kozłowska et al, 2016). Palynological studies have shown that these grey deposits correspond to the Rhaetian character of the waning episode of Triassic sedimentation (Kozłowska et al, 2016).…”
Section: Lithology Mineralogy Physical and Mechanical Properties Of T...mentioning
confidence: 95%
“…The Upper Triassic deposits are siliciclastics (claystones, mudstones and sandstones of fluvial, lacustrine and playa origin) with a wide range of colours (mainly red and greenish) belonging to an informal lithostratigraphic unit-Keuper (Deczkowski & Franczyk, 1988;Fijałkowska, 1992;Fijałkowska-Mader, 2013;Kopik, 1970;Pawłowska, 1979;Pie nkowski, 2009). Because these deposits have a negligible fossil content, their exact stratigraphic position is imprecise, although they are commonly referred to as 'Rhaeatian' (Krupnik et al, 2014;Marcinkiewicz et al, 2014;Marcinkiewicz & Orłowska-Zwoli nska, 1985Orłowska-Zwoli nska, 1983) (Kozłowska et al, 2016). Palynological studies have shown that these grey deposits correspond to the Rhaetian character of the waning episode of Triassic sedimentation (Kozłowska et al, 2016).…”
Section: Lithology Mineralogy Physical and Mechanical Properties Of T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mineralogical studies of siderite interbeds in Middle Jurassic siliciclastic rocks from the Polish Lowlands were conducted by Maliszewska [19] and Maliszewska et al [20][21][22][23]. Kozłowska's studies provided petrographic analyses of siderite rocks from the northeastern margin of the Holy Cross Mountains [24][25][26][27][28][29][30] and the Częstochowa region [26,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Feldman-Olszewska [26,31] and Leonowicz [37][38][39][40] conducted sedimentological analyses of Middle Jurassic deposits in the Częstochowa region. Single publications contain sedimentological data on rocks containing Middle Jurassic siderite interbeds in the northeastern margin of the Holy Cross Mountains [25].…”
Section: Introductionmentioning
confidence: 99%